Hybridizing a Multi Response Taguchi Algorithm with Reference Ideal Method to Solve Machining Problems - SOFUOGLU, Mehmet Alper (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Multi criteria decision making models (MCDM) are extensively used in material-process selection, and optimization in machining problems in engineering. In this study, a novel hybrid optimization model is developed. Taguchi method is hybridized with Reference Ideal Method. The model is tested in case studies taken from literature. The developed model produced similar results with literature. The proposed model can be used by engineers and operators in manufacturing environment.